Cystargamide B, a cyclic lipodepsipeptide with protease inhibitory activity from Streptomyces sp. (July 2018) - Kitani, Shigeru; Yoshida, Mitsuki; Boonlucksanawong, Ousana; Panbangred, Watanalai; Anuegoonpipat, Atchareeya; Kurosu, Takeshi; Ikuta, Kazuyoshi; Igarashi, Yasuhiro; Nihira, Takuya
Abstract We identified a new cyclic lipodepsipeptide, cystargamide B (1 ), from the mycelial extract of aKaempferia galanga rhizome-derived actinomycete strain, Streptomyces sp. PB013. The planar structure was elucidated based on high resolution fast-atom bombardment mass spectrometry (HRFABMS) spectroscopy and one-dimensional (1D) and two-dimensional (2D) nuclear magnetic resonance (NMR) spectroscopic data. The absolute configurations of the constituent amino acids were determined using advanced Marfey's method. Cystargamide B (1 ) includes rare structural units: a 5-hydroxytryptophan residue and a 2, 3-epoxy fatty acid side chain. Notably, cystargamide B (1 ) inhibited the protease activity of the NS2B/NS3 complex from dengue virus.